Contemplative investigation into Christ consciousness with Heart Prayer and HeartMath practices - Edwards, Stephen D. (HTS teologiese studies, 2017)
An exploratory pilot study with a small homogenous sample of Christian English speaking participants (four men and four women, with a mean age of 48 and age range from 27 to 70 years) provided support for an alternative research hypothesis that a Christ consciousness contemplation with Heart Prayer of HeartMath techniques was significantly associated with increasing psychophysiological coherence, sense of coherence, spirituality and health perceptions. Participants described feelings of a peaceful place in oneness and connection with Christ. Integrative findings point towards Christ consciousness as an ultimately non-dual process of sensing vibrational resonance radiating from the human heart. Implications for further research are discussed.